A retrospective evaluation of the effects of COVID-19 vaccines on the CRP, IL-6, ferritin, and D-dimer levels of patients admitted to the COVID intensive care unit - Yasemin Bozkurt Turan (Medicine Science)
With its elevated mortality and morbidity rates and various complications, the highly contagious Corona Virus Disease - 2019 (COVID-19) infection that developed in association with the agent severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) led to the world's most deadly pandemic. However, COVID-19-related mortality declined with the development of vaccines. Elevated D-dimer, C-reactive protein (CRP), ferritin, interleukin-6 (IL-6) values in patients with COVID-19 pneumonia are markers that need to be monitored in terms of both severity of infection and prognosis. This article investigates the relationship between COVID-19 vaccination and these parameters. This retrospective, cross-sectional study involved patients aged over 18 diagnosed with COVID-19 pneumonia and admitted to a tertiary COVID intensive care unit. These were assigned to vaccinated or unvaccinated groups, as applicable. The vaccinated patient group was also divided into two subgroups, those who had been given the inactive COVID-19 vaccine and those administered the messenger RNA (mRNA) COVID-19 vaccine. Median age and the proportion of female patients (54.1%) were both higher in the vaccinated patient group. Higher rates of chronic obstructive pulmonary disease and hypertension were also observed in the vaccinated group. Median length of hospital stay and mortality rates (85.5%) were higher in the unvaccinated patient group. The median length of stay was lower in both the group given twin doses of mRNA COVID-19 vaccine and in the patients given the inactive COVID-19 vaccine. Significantly lower median D-dimer levels were determined in the vaccinated patient group (1.3 mg/L) and in the patients administered two doses of inactive COVID-19 vaccine (1.1 mg/L). D-dimer levels among patients admitted to the COVID intensive care unit were higher in the unvaccinated group and in those who had been given a single dose of inactive COVID-19 vaccine, and this represented a risk in terms of mortality. [Med-Science 2025; 14(1.000): 74-80]